The final spectacle military painting under the Second Empire, 1855-1867 - Thoma, Julia ca. 20. Jh (De Gruyter, 2019)
The book examines military paintings in France in the 1850s and 1860s, when the genre experienced a new lease of life. It recreates the paintings’ art-historical, historical and social context, and considers the explosion of military subjects in their own right rather than as a consequence of war reporting. The paintings’ entertainment value effectively communicated political agendas, catering to the emerging phenomenon of mass spectatorship and giving rise to innovative compositions. The book also looks at the other side of the artistic spectrum, proposing that smaller formats adapted the sentimental techniques of military memoirs to focus on the soldiers’ experiences of warfare and to elicit a critique of war